Electrochemical behavior of lead and cadmium in aqueous solitions containing Triton X-100 and aliphatic alcohols - V. A. Bacun; D. M. Fedulov; E. A. Osipova; N. K. Zaytsev; I. Yu. Lovchinovski (Тонкие химические технологии)
The stripping voltammetry on the mercury film electrode with the change of the solution without of the opening of the electrochemical circuit was applied to characterize the behavior of Pb (II) and Cd (II) in aqueous solutions, containing Triton X-100 and aliphatic alcohols, namely ethyl, n-propyl, n-butyl, and n-amyl alcohol. The effect of the length of the hydrocarbon chain in the alcohol on the peak current of Pb (II) and Cd (II) was studied. The presence of Triton X-100 eliminates the interference of alcohols while stripping analysis of Pb (II) and Cd (II) due to the formation of mixed micelles